FORMATION OF LEXICAL COMPETENCE IN TEACHING ENGLISH AS A SECOND FOREIGN LANGUAGE - Ismoilova Shahnoza Abdumalik qizi (Research Focus International Scientific Journal, 2022)
The modern linguistic situation, characterized by the growth of multilingualism, has awakened an increased research interest in the phenomenon of linguistic interference that occurs in the study of foreign languages. To date, there are a large number of studies devoted to the influence of the native language on the study of a foreign language, but the problem of the interaction of two studied foreign languages ​​with each other is not covered enough. The article is devoted to the formation of lexical competence in teaching English for professional purposes to international students who previously studied French, taking into account interlingual interference. Long-term pedagogical practice allowed us to assume that in the study of diplomatic terminology, lexical interference will arise and play a significant role, the source of which is the French language. The author puts forward a hypothesis that the process of forming lexical skills will be more effective if a teaching methodology is built taking into account the transfer of skills and abilities from FL1, with the inclusion in the educational process of a set of exercises for mastering vocabulary based on an authentic text. The author comes to the conclusion about the expediency of developing a special educational and methodological complex for teaching a second foreign language and offers his own version, which combines the use of an integrative set of exercises for teaching vocabulary in the process of intensive reading with the methodology of critical pedagogy. The author presents the results of a pilot study confirming the effectiveness of the proposed methodology in terms of forming lexical skills, expanding vocabulary and reducing the number of errors associated with language interference.